From mainframes to smartphones : a history of the international computer industry - Campbell-Kelly, Martin; Garcia-Swartz, Daniel D., 1962- (Critical issues in business history., 2015)
"The aim of this book is to provide a compact and up-to-date business and economic history of the computer industry. The reader we have in mind is someone who wants to make a "quick study" of the computer industry ... In our quest for brevity, we have assumed that our readers are themselves information-technology users and are familiar with the everyday vocabulary of computing (such as "operating systems," "disk drives," and "broadband"), and that they are aware of recent gadgetry such as tablet computers and smartphones"--Page 1